Circadian rhythm of serum interleukin-6 in rheumatoid arthritis. Issue 8 (August 1994) - Arvidson, N G; Gudbjörnsson, B; Elfman, L; Rydén, A C; Tötterman, T H; Hällgren, R
Abstract : OBJECTIVES--To test the hypothesis of a diurnal variation in circulating levels of interleukin-6 (IL-6) and/or tumour necrosis factor-alpha (TNF-alpha) in rheumatoid arthritis and other inflammatory connective tissue diseases. METHODS--Serum levels of IL-6 and TNF-alpha were measured at three hour intervals from 7:30 to 22:30 in 48 patients with different rheumatic diseases as well as ten healthy controls. In four of the patients with rheumatoid arthritis, serum IL-6 levels were measured before and after one week of treatment with prednisolone 15-20 mg daily. RESULTS--IL-6 and TNF-alpha could not be detected in serum from healthy controls. However, serum IL-6 levels were substantially increased in patients with rheumatoid arthritis. Furthermore, patients with rheumatoid arthritis showed a statistically significant circadian variation in levels of IL-6. Peak values appeared in the morning and low values in the afternoon and evening. In contrast, levels were low and stable in other connective tissue diseases. Levels of TNF-alpha were low in patients with rheumatoid arthritis and high in patients with other connective tissue diseases, but without circadian rhythm. After treatment with prednisolone, levels of serum IL-6 decreased significantly, but the circadian rhythm remained. CONCLUSIONS--The circadian rhythm of circulating IL-6 might correspond to the circadian rhythm of symptoms in rheumatoid arthritis. The diurnal variation of IL-6, and possibly other cytokines, might explain the conflicting results previously reported on the inter-relationship between circulating IL-6 levels and disease activity in rheumatoid arthritis.